THE EFFECT OF OZONE BAGGING THERAPY ON WOUND HEALING IN DIABETIC ULCER PATIENTS - mufarika mufarika; Faisal Amir Amir; Zuryaty Zuryaty; Abdul Muhyi; Agus Haryanto; Merina Widyastuti (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2022)
ABSTRACT Diabetes mellitus with diabetic ulcers can cause complications, namely susceptibility to infection, pulmonary tuberculosis, and infections of the feet. Chronic complications include diabetic feet with the risk of foot ulcers (diabetic ulcers) and resulting in amputation, these diabetic feet can develop into gangrene. This study aims to analyze the effect of wound healing on diabetic ulcer patients who are given ozone bagging therapy. The research design used a quasy-experimental design with pre-test and post-test with control group design. Population 30 respondents. The number of samples taken is 26 respondents. The sampling technique used is probability sampling with the Simple Random Sampling technique. The data collection technique used a questionnaire sheet. Statistical test using Man-Whitney test with (a=0.05). This research has been carried out Ethical clearance tested by the KEPK STIKes Ngudia Husada Madura. The results showed that based on the Man-Whitney statistical test with test results (p= 0.021) < (a = 0.05). So it can be concluded that there were differences in wound healing in diabetic ulcer patients in the control group (without ozone bagging therapy) and the treatment group (with ozone bagging therapy). It is suggested that this research can be used as a reference regarding wound healing in diabetic ulcer patients who are given ozone bagging therapy and can motivate patients with diabetes mellitus in controlling blood sugar levels, as well as serve as information about one way that can be done in controlling blood sugar levels daily. Keywords: Ozone Bagging, Diabetic Ulcer, Diabetes Mellitus, Wound Healing